Consumer perceptions of food quality in Malaysia - Chamhuri, N.; Batt, Peter (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to gain an understanding of the quality cues that consumers look for in purchasing fresh meat and fresh fruit and vegetables in Malaysia. Through a perceived quality model, this paper identifies the implicit, intrinsic, extrinsic and credence quality cues consumers’ use in their decision to purchase fresh meat and fresh fruit and vegetables. Design/methodology/approach – This study utilised the shopping mall intercept survey method. Data were collected from traditional markets and modern retail outlets in the Klang Valley region in Malaysia. A structured questionnaire was designed to measure consumer’s perceptions and experiences of food quality when purchasing fresh meat and fresh fruit and vegetables from retail outlets. In this study, univariate data analysis (descriptive analysis, one-way analysis of variance) and exploratory factor analysis were performed to analyse the data sets. Findings – Freshness (intrinsic cue), was the most frequently cited variable when respondents thought about the quality of both product categories. Other variables included price and cleanliness (extrinsic cues) and Halal (credence cue), which was associated with the quality of fresh meat. Quality was associated with freshness, food safety, nutrition and value. Exploratory factor analysis identified food safety (implicit cue) as the most important construct in the respondents’ evaluation of quality for both fresh meat and fresh fruit and vegetables. Originality/value – There is a paucity of research focusing on consumer’s perceptions and experiences of food quality in the purchase of fresh meat and fresh produce in Malaysia. The findings of this research may assist the Malaysian food industry by providing new insights into the consumers’ perceptions of food quality.